2013
DOI: 10.1080/17429145.2013.820360
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid impairs rhizogenesis and root growth, and alters associated biochemical changes in mung bean (Vigna radiata) hypocotyls

Abstract: The present study investigated the effect of ferulic acid (FA; 0Á1000 mM) on early growth, and rhizogenesis in mung bean (Vigna radiata) hypocotyls and associated biochemical changes. FA severely affected the radicle elongation and number of secondary roots after 72 h. The root and shoot length, number and length of secondary roots, and seedling dry weight of one-week-old seedlings of mung bean were decreased by 64%. The rooting potential (percent rooting, number and length of adventitious roots) of mung bean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…Upon infection by pathogens, the host phenolic compounds may increase and contribute to enhance the mechanical strength of host cell walls by the synthesis of lignin and suberin that are involved in the formation of physical barriers that can block the spread of pathogens (Ngadze et al, 2012;Singh et al, 2014). In the present study, the amount of total phenol was significantly higher in virus infected leaves (Fig.…”
Section: Total Phenolmentioning
confidence: 47%
“…Upon infection by pathogens, the host phenolic compounds may increase and contribute to enhance the mechanical strength of host cell walls by the synthesis of lignin and suberin that are involved in the formation of physical barriers that can block the spread of pathogens (Ngadze et al, 2012;Singh et al, 2014). In the present study, the amount of total phenol was significantly higher in virus infected leaves (Fig.…”
Section: Total Phenolmentioning
confidence: 47%
“…Phenolic compounds may contribute to enhance the mechanical strength of host cell walls by the synthesis of lignin and suberin that are involved in the formation of physical barriers that can block the spread of pathogens (Ngadze et al 2012;Singh et al 2014). In the present study, the amount of total phenols was significantly higher in leaves of noninoculated and inoculated plants of both resistant genotypes (Ravi and Co Tiep Khac), while it was significantly lower in susceptible genotypes (CIM-496 and NIAB-111; Figure 1A).…”
Section: Total Phenolsmentioning
confidence: 99%
“…A number of reports are available that indicate an increased activity of POXs in response to phenolic compounds. For example, seedlings treated with ellagic, ferulic or cinnamic acids under both normal or abiotic stress conditions was found to significantly enhance POX activity (Li et al, 2011;Abu El-Soud et al, 2013 andSingh &Kaur, 2014). Also, we found that coumarin seed pretreatment caused obvious stimulation in the activities of both PAL and POX in wheat seedlings under salinity stress .…”
Section: Discussionmentioning
confidence: 58%
“…Also in a previous study, we found that application of 1.0 mM coumarin significantly enhance the activities of both amylase and protease as well as the accumulation of soluble sugars and proteins in Vicia faba seedlings under salt stress (Saleh et al, 2014). Other study showed that ferulic acid increased the activity of proteases in mung bean hypocotyls (Singh & Kaur, 2014). Similarly, pretreatment of cucumber seedlings with 0.5 mM ferulic acid had protected them from dehydration stress and resulted in accumulation of soluble sugars in their leaves (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 64%